The Effect of Aggregate Micro and Macrotexture on Pavement Skid Resistance in UTHM Campus Pagoh - Idurus, Iqbal Akmal; Safuan, Muhammad Aidil Fikri; Jamaluddin, Muhammad Fareez Syahmi; Bujang, Hazirah (Multidisciplinary Applied Research and Innovation, 2025)
Skid resistance is very important for driver safety. Friction force between vehicle’s tires with the road surface can prevent tires from rolling slides along road surfaces. Road accidents are a global problem, resulting in millions of deaths and injuries every year. This can happen because pavement skid resistance values are below a minimum safe level. In wet weather conditions, the number of accidents will be increased because of skid resistance. The aim of this study is to study the effect of aggregate micro and macro texture on pavement skid resistance of UTHM Campus Pagoh. The tests were carried out by using British Pendulum Test method and Sand Patch Method following the ASTM E303 and ASTM E965 respectively. The skid resistance values were analyzed and has been determined whether the skid resistance value of the road pavements inside the campus is safe to use or not. The skid resistance value plays an important role towards the safeness of the roads.